Uncle John's city garden - Ford, Bernette G.; Morrison, Frank, 1971- (New York : Holiday House, 2022)
While visiting her uncle John in the city for the summer, an African American girl, L'il Sissy, her siblings, and uncle transform an empty lot into a vegetable garden. Includes recipe for succotash.
Booklist starred
Horn Book
Kirkus Review
Booklist starred, May 2022
Horn Book, May 2022
Kirkus Review, February 2022
Keywords: African Americans -- Juvenile fiction; City and town life -- Juvenile fiction; Gardening -- Juvenile fiction; Gardens -- Juvenile fiction; African Americans -- Fiction; City and town life -- Fiction; Gardening -- Fiction; Gardens -- Fiction; African Americans -- Fiction; City and town life -- Fiction; Gardening -- Fiction; Gardens -- Fiction; Picture books